Case management of childhood fever by traditional healers in Southwest Nigeria: Identification of training and collaborative needs (2008)
Traditional healers play an important role in the provision of healthcare in many communities in Africa. This study aimed to improve home management of malaria in children by assessing the healer's knowledge and practice. A semi-structured questionnaire interview of 127 traditional healers selected by proportionate sampling technique from two rural and two urban local government areas (LGAs) of southwestern Nigeria was followed by a training program. Malaria ranked first (87%) among the illnesses managed by the healers. Diagnosis of fever was often (72%) based on client history, physical examination (24.4%), consulting oracles (18.9%), and interpretation of dreams (3.1%). Treatment of malaria was with boiled herbs ("agbo"; 72%), ground herbs ("agunmu"; 14%), and incisions and scarifications (3%). Forty-one (32.5%) healers had referred febrile children to a health facility. Younger healers and those who had at least a secondary education were more likely to refer patients (p < 0.05 in both cases). Thirty-six healers (28.4%) had previous formal training on management of fevers, most of whom were the younger (p < 0.(5), educated healers (p> 0.05), with fewer years of practice (p> 0.05). Research into traditional herbs (48%), better acknowledgment by government (23.6%); and collaboration with other health sectors were suggestions to improve practice. Traditional healers, especially the older, less-educated, and long-practicing healers, urgently require formal training and collaboration with other healthcare providers to improve knowledge and promote early referral of children with fever.